1991
DOI: 10.2527/1991.6962634x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of body weight, forage composition, and corn supplementation to feed intake and digestion by Holstein steer calves consuming bermudagrass hay ad libitum.

Abstract: Holstein steer calves (101 to 350 kg BW) consumed bermudagrass hay ad libitum without or with supplemental ground corn up to 1.0% of BW. As BW increased, total DMI increased quadratically (-2.459 + .05448 [BW]-.000073 [BW2] + .540 [corn DMI]; R2 = .83, sy.x = .655). Each kilogram of corn DM decreased bermudagrass DMI by .46 kg. Total digestible OM intake (kg) increased with BW and corn supplementation (.314 + .0127 [BW] + .441 [corn OM intake]; R2 = .79, sy.x = .444). Feed intake level accounted for approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Estimated DMI in low quality bahiagrass diet, however, did not correlated (R 2 = 0.075; P < 0.306) with BW (Figure 2(b)). Goetsch et al [9] reported that as BW increased, total DMI (kg) increased quadratically in Holstein steer. Likewise, the kilograms of Bermudagrass DM consumed increased quadratically with increasing BW.…”
Section: Itemsmentioning
confidence: 99%
“…Estimated DMI in low quality bahiagrass diet, however, did not correlated (R 2 = 0.075; P < 0.306) with BW (Figure 2(b)). Goetsch et al [9] reported that as BW increased, total DMI (kg) increased quadratically in Holstein steer. Likewise, the kilograms of Bermudagrass DM consumed increased quadratically with increasing BW.…”
Section: Itemsmentioning
confidence: 99%
“…This increase in total DMI has been observed for cattle that are either grazing or fed high forage diets and supplemented with concentrate or fiber-based supplements Bodine et al, 2001;Sanson and Clanton 1989;Matejovsky and Sanson, 1995;Gekara et al, 2001;Goetsch et al, 1991). Most feeds have substitution rates that are less than one and greater than zero Bodine et al, 2001;Sanson and Clanton 1989;Matejovsky and Sanson, 1995;Gekara et al, 2001;and Goetsch et al, 1991) which results in a net increase in total DMI and increased animal productivity. observed that dairy cows grazing at high and low pasture allowances had increased total DMI as concentrate was supplemented at 8.63 kg/d.…”
Section: Effects Supplementation On Total Dry Matter Intakementioning
confidence: 85%
“…Bodine et al (2001) found that steers supplemented with protein increased total OM intake and improved BW gain. In spite of substitution, total DMI is quite often increased, even with cattle at different stages of production and consuming forages of different quality as indicated by reported substitution rates less than one Bodine et al 2001;Sanson and Clanton 1989;Gekara et al 2001;and Goetsch et al 1991). Only in certain situations, such as supplementation of low quality forage with high protein supplement, can an increase in forage intake be observed as well.…”
Section: Effects Supplementation On Total Dry Matter Intakementioning
confidence: 99%
See 2 more Smart Citations